The role of pre-accession assistance in the process of joining the European Union - Marko Aćić; Miloš Grujić (Acta Politica Polonica, 2023)
This paper primarily analyzes the classification of international organizations according to different criteria to see the specificity of the EU as a sui generis international organization. The authors specifically examine the legal order of the EU and the process of achieving full membership. They are interested in the EU accession process, particularly for countries in the Western Balkans like Bosnia and Herzegovina, which is covered by the Stabilization and Association Agreement. Candidate countries have access to various EU funds, which the authors analyze as pre-accession assistance. The study assesses Bosnia and Herzegovina’s status in European integration and delves into the use of IPA funds in the country, including its withdrawal, scope, and limitations. The authors emphasize the importance of IPA funds for Bosnia and Herzegovina.